Evolution of "State Ruling". (21st May 2015) - Caya, Sinan
Abstract: The concept of ruling a state was investigated by Machiavelli as early as in the sixteenth century. The concept gradually developed throughout centuries and finally achieved a certain level of maturity in today's politics.